Two new species of medeventor wheeler from South America (Diptera, chloropidae, oscinellinae) - Bazyar, Zeinab; Silva, Vera Cristina [UNESP] (Magnolia Press, 2018)
The oscinelline genus Medeventor Wheeler, 2007 was originally proposed for a single quite aberrant species from Central America, M. nubosus Wheeler, 2007. In this paper, we present two new Brazilian species of Medeventor—M. minimus sp. n. and M. tschirnhausi sp. n. (both from the State of Mato Grosso). A key for the species of the genus is provided. Some comments are made on the diagnosis of the genus.
Keywords: Brazil; Identification key; Neotropical region; New record; New species